2020
DOI: 10.1038/s41467-020-16786-5
|View full text |Cite
|
Sign up to set email alerts
|

A kinase-deficient NTRK2 splice variant predominates in glioma and amplifies several oncogenic signaling pathways

Abstract: Independent scientific achievements have led to the discovery of aberrant splicing patterns in oncogenesis, while more recent advances have uncovered novel gene fusions involving neurotrophic tyrosine receptor kinases (NTRKs) in gliomas. The exploration of NTRK splice variants in normal and neoplastic brain provides an intersection of these two rapidly evolving fields. Tropomyosin receptor kinase B (TrkB), encoded NTRK2, is known for critical roles in neuronal survival, differentiation, molecular properties as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 86 publications
2
31
0
Order By: Relevance
“…[11][12][13] Kinases have been shown to play important roles in gliomagenesis. [14][15][16] The understanding of kinase-related mechanism will help us to develop a new strategy against glioma.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Kinases have been shown to play important roles in gliomagenesis. [14][15][16] The understanding of kinase-related mechanism will help us to develop a new strategy against glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma is a prevalent intracranial malignancy contributes to considerable cancer-related mortality [6,27]. Meanwhile, it is characterized by insensitive to conventional chemo-radiotherapy [28,29]. CircRNA is a class of noncoding RNA generated from a non-canonical back splicing process, from a covalent bond between 5' and 3' ends of a single-stranded RNA [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of NTRK2 was documented in patient-derived breast cancer murine xenografts, in brain-trophic triple negative breast cancer cell lines, and in brain metastases from patients with breast cancer 8 . Mutations of NTRK2 have been found in pilocytic astrocytomas 9 , and splice variants of NTRK2 deficits in kinase activity have been discovered in gliomas, indicating importance of NTRK2 in human cancers of the brain 10 . Interestingly, one study suggested that HER2 and NTRK2 may be capable of heterodimerizing; phosphorylated NTRK2 was observed at relatively higher levels than total NTRK2 in brain metastatic tissues, and phosphorylated HER2 and phosphorylated NTRK2 were observed at significantly higher levels in HER2+ breast cancers as compared to triple negative breast cancers in a small subset of patient tumors 11 .…”
Section: Discussionmentioning
confidence: 99%